2023
DOI: 10.1111/ahg.12532
|View full text |Cite
|
Sign up to set email alerts
|

Low‐pass whole genome sequencing is a reliable and cost‐effective approach for copy number variant analysis in the clinical setting

Patricia C. Mazzonetto,
Darine Villela,
Silvia Souza da Costa
et al.

Abstract: IntroductionNext generation sequencing technology has greatly reduced the cost and time required for sequencing a genome. An approach that is rapidly being adopted as an alternative method for CNV analysis is the low‐pass whole genome sequencing (LP‐WGS). Here, we evaluated the performance of LP‐WGS to detect copy number variants (CNVs) in clinical cytogenetics.Materials and MethodsDNA samples with known CNVs detected by chromosomal microarray analyses (CMA) were selected for comparison and used as positive co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In this study, we applied LP-WGS in a large multicentric Brazilian cohort in order to evaluate the costeffectiveness of this approach as a diagnostic alternative to replace CMA and provide more equal access to genetic testing in our country. Notably, the diagnostic yield (P/LP CNVs) in this cohort (16%) is comparable to the 15-20% determined for CMA and the CNV detection rate is highly e cient, costing only a quarter of CMA 14 . Regarding the frequency of VUS, it is estimated in approximately 6% from postnatal microarrays 32 , similar to our ndings with LP-WGS.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…In this study, we applied LP-WGS in a large multicentric Brazilian cohort in order to evaluate the costeffectiveness of this approach as a diagnostic alternative to replace CMA and provide more equal access to genetic testing in our country. Notably, the diagnostic yield (P/LP CNVs) in this cohort (16%) is comparable to the 15-20% determined for CMA and the CNV detection rate is highly e cient, costing only a quarter of CMA 14 . Regarding the frequency of VUS, it is estimated in approximately 6% from postnatal microarrays 32 , similar to our ndings with LP-WGS.…”
Section: Discussionsupporting
confidence: 50%
“…In our previous work, we showed that LP-WGS, also known as shallow sequencing, is equally sensitive and accurate as CMA in detecting copy number changes both in prenatal and postnatal samples 14 . LP-WGS is already widely applied in multiple international diagnostic centers for CNV detection in a variety of clinical applications, including NIPT 27 , pre-implantation genetic testing 28 , liquid biopsy 29 , and solid tumor analysis 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations